2023
DOI: 10.1021/acs.nanolett.2c04752
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable and Skin-Mountable Temperature Sensor Array Using Reduction-Controlled Graphene Oxide for Dermatological Thermography

Abstract: Since thermometry of human skin is critical information that provides important aspects of human health and physiology, accurate and continuous temperature measurement is required for the observation of physical abnormalities. However, conventional thermometers are uncomfortable because of their bulky and heavy features. In this work, we fabricated a thin, stretchable array-type temperature sensor using graphene-based materials. Furthermore, we controlled the degree of graphene oxide reduction and enhanced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In addition, conductive nanoparticles [69] (Pt, Ni, Al), graphene [70], hydrogels [71], and ion liquid are commonly employed as resistive thermo-sensitive materials. The band gap structure and oxygen functional groups of reduced graphene oxide can be regulated by adjusting the degree of reduction, resulting in different temperature coefficients [72]. Jia et al have reported a serious of thermal sensors based on ion liquids, including 1-ethyl-3-methylimidazolium acetate ([EMIm][Ac]) [73], green electrolytes [28] and 1-Ethyl-3-methylimidazolium bis(trifluoromethyl sulfonyl)imide ([EMIm][Tf 2 N]) [74], which exhibit electrical conductivity increasement with temperature increasing.…”
Section: Temperature Sensorsmentioning
confidence: 99%
“…In addition, conductive nanoparticles [69] (Pt, Ni, Al), graphene [70], hydrogels [71], and ion liquid are commonly employed as resistive thermo-sensitive materials. The band gap structure and oxygen functional groups of reduced graphene oxide can be regulated by adjusting the degree of reduction, resulting in different temperature coefficients [72]. Jia et al have reported a serious of thermal sensors based on ion liquids, including 1-ethyl-3-methylimidazolium acetate ([EMIm][Ac]) [73], green electrolytes [28] and 1-Ethyl-3-methylimidazolium bis(trifluoromethyl sulfonyl)imide ([EMIm][Tf 2 N]) [74], which exhibit electrical conductivity increasement with temperature increasing.…”
Section: Temperature Sensorsmentioning
confidence: 99%
“…The first is the field where the tactile e-skin is attached to the real human skin, and the second is the field where the tactile e-skin is attached to the surface of bionic human skin. In fact, the tactile e-skin used in both fields has a high demand for breathability. Currently, there are remarkable application cases of tactile e-skin attached to real skin, which have different sensing principles, have flexible structures, and are made of functional materials. Moreover, tactile e-skin has broad application prospects in medical treatment, sports monitoring, and quantitative perception of tactile pressure on the body surface.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible sensors present substantial technological opportunities, such as monitoring temperature distribution over a large surface area through tape-like attachment of sensors to target objects. , However, covering extended areas implies the requirement for numerous sensors, fueling the need for low-cost fabrication approaches such as printing or transfer methods. To date, various cost-effective flexible temperature sensors have been reported in the literature that use metal-, semiconductor-, and composite-based material systems, each with distinct characteristics in terms of long-term stability and high sensitivity. ,, Graphene oxide mixed with poly­(ethylene oxide) and poly­(vinylidene fluoride) has been employed in sensing devices, exhibiting a high sensitivity of ∼11.2%/°C . Long-term stability was achieved by employing carbon nanotube and SnO 2 nanoparticles; however, the sensitivity (∼0.23%/°C) is sacrificed to realize high stability.…”
Section: Introductionmentioning
confidence: 99%